Assessing children’s native language in Mandarin using the adapted New Reynell Developmental Language Scales-Mandarin (NRDLS-M) - Lim, Hui Woan; Lee, Soon Tat (Penerbit Universiti Kebangsaan Malaysia, 2017)
Early child language acquisition in Mandarin by Malaysian Chinese children is underexplored. Following the establishment of the first Speech Sciences academic programme at Universiti Kebangsaan Malaysia (UKM) in 1994, there is a need to develop language tests to assess children who might be at risk for language disorders and to provide remediation accordingly by professionals such as speech therapists. The present study aims to adapt a contemporary British English test: The New Reynell Developmental Language Scales (NRDLS) to Mandarin. Since NRDLS is widely-used to assess language comprehension and language production, the aim of the present research therefore is to propose adaptation of NRDLS to Mandarin. The present research also aims to provide preliminary norms (age of acquisition for target structures and errors) for the local children. Underlying factors which might influence child language development i.e. age, gender and socio-economic status (maternal education) are also examined. Using a cross-sectional study of 40 children aged 2;00-6;11, the present study aims to describe child language acquisition based on performance of the adapted NRDLS. The present results show that language skills advanced with age. Gender and maternal education do not affect child language development. Overall, children demonstrated a more superior language comprehension than language production. The adapted New Reynell Developmental Language Scales-Mandarin (NDRLS-M) is developmentally sensitive though further revisions are required. The present findings implicate an influence of universality and ambient language effects on acquisition of Mandarin. The present findings also implicate a need to develop a bilingual Mandarin- English version of NRDLS-M.